Os afetos como critério de vinculação familiar no Direito da Família português - Pina, Catarina Isabel da Costa (2021)
The present report focuses, essentially, on “affection” as one of the family bonding criteria and that, in view of the transformations of society that led to a new and broad interpretation of the concept of “family”, considering the admission of new forms of family and the principle of the child's best interest, it has been shown to be a determining factor in establishing affiliation, since the biological ties have ceased to be so, to establish the legal ties of affiliation. Initially, a brief reference will be made to the evolution of the concept of "family" and the rise of affections in Portuguese Family Law. It will be observed, both in Portuguese Family Law and in the light of the jurisprudence of the European Court of Human Rights, the inclusion of affection as one of the family bonding criteria. On the other hand, using Brazilian Law, socio-affective affiliation will be emphasized, namely the possession of the status of a child, derived from the bonds of affection built in lasting family life, as a basis for establishing paternity and motherhood, always in view of the child's best interests. Finally, it will be observed that, although Portuguese Law, since the 1977 Reform, express an interest in coinciding the legal truth with the biological truth, the biological truth is not absolute and that not all paternity or maternity results from biological bonds, since it is possible to identify several examples of manifestation of affection as a criterion for family ties, among the various exceptions to biological truth. In view of the above, the possibility developed that socio-affective affiliation, especially the possession of the status of a child (presuppositions: “nomen”, “tractatus” and “fama”), derived from the bonds of affection built in lasting family life, could be recognized in the Portuguese legal system as a foundation for establishing paternity and maternity, but also to prevent the impugnation of affiliation, always taking into account the child's best interests.